2019
DOI: 10.1097/hjh.0000000000001933
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pulse wave velocity trajectories from youth to young adulthood

Abstract: Objective: Increased arterial stiffness measured by pulse wave velocity (PWV) has been shown to be an important parameter of cardiovascular risk. Longitudinal development of PWV from youth to early adulthood and its possible sociodemographic, anthropometric, hemodynamic and behavioral moderators will be illustrated. Methods: Individual growth curves of carotid–distal PWV across age were created for 559 African American and European American men and women with a maximum of five assessments over an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
3
17
0
1
Order By: Relevance
“…Our current cohort study provided further support for this concept in the adolescent population. A previous study 29 revealed that the marital status of parents was the strongest socioeconomic predictor of young adult arterial stiffness, and we found the TG level was higher in single-parent adolescents. In addition, the relationship between parental education and the cardiovascular risk of adolescent is controversial, and our results showed a positive relationship between parental education or family income and FI or IR.…”
Section: Discussionsupporting
confidence: 62%
“…Our current cohort study provided further support for this concept in the adolescent population. A previous study 29 revealed that the marital status of parents was the strongest socioeconomic predictor of young adult arterial stiffness, and we found the TG level was higher in single-parent adolescents. In addition, the relationship between parental education and the cardiovascular risk of adolescent is controversial, and our results showed a positive relationship between parental education or family income and FI or IR.…”
Section: Discussionsupporting
confidence: 62%
“…Elevated blood pressure level during childhood and adolescence is a recognized predictor of adulthood BP, leading to increased CVD disease in adults [1,2]. It is imperative to study the prevalence and risk factors for childhood and adolescents' hypertension, especially in low social economic status (SES) population.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the physical examination have been described previously [ 23 ]. The mean arterial pressure (MAP) was calculated as 1/3 systolic blood pressure plus 2/3 diastolic blood pressure [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence rates of overweight and obesity were 11.7% and 6.8%, respectively, in 2011–2015 among children and adolescents in China [ 3 ]; the prevalence continues to increase, particularly in urban areas, and is accompanied by an increase in family income and changes in modern lifestyles [ 3 ]. A long-term cohort study found that obesity is the risk factor most strongly associated with a large carotid intima media thickness (cIMT) and an increased pulse wave velocity (PWV) in young adulthood [ 4 , 5 ], and a large cIMT is an index of an increased risk of cardiovascular disease (CVD) in adulthood. Additionally, children and adolescents with obesity may have psychiatric disorders [ 6 ], which may increase the risk of suicide and antisocial behavior in adolescents and adulthood.…”
Section: Introductionmentioning
confidence: 99%